Anodic Potential and Conversion Chemistry of Anhydrous Iron (II) Oxalate in Na-Ion Batteries - Vasilii Gromov; Atlas Noubir; Fatemeh Keshavarz; Ekaterina Laakso; Bernardo Barbiellini; Arun Bansil (Condensed Matter, 2023)
Anhydrous ferrous (II) oxalate (AFO) outperforms its hydrated form when used as an anode material in Li-ion batteries (LIBs). With the increasing interest in Na-ion batteries (NIBs) in mind, we examine the potential of AFO as the anode in NIBs through first principles calculations involving both periodic and non-periodic structures. Our analysis based on periodic (non-periodic) modeling scheme shows that the AFO anode generates a low reaction potential of 1.22 V (1.45 V) in the NIBs, and 1.34 V (1.24 V) in the LIBs, which is much lower than the potential of NIBs with mixed oxalates. The conversion mechanism in the underlying electrochemical process involves the reduction of Fe<semantics>2+</semantics> with the addition of Na or Li. Such conversion electrodes can achieve high capacities through the Fe<semantics>2+</semantics> valence states of iron.